Microseismic voltage evolution of composite coal rock under load deformation failure - Xin LI; Zhiyong LIU; Zhen YANG; Hao LI; Jing ZHOU; Jingran BU; Yiru WANG; Zhongming ZHUANSUN (Meitan xuebao)
During the deformation and rupture process of loaded composite coal rock, due to the generation and expansion of fissures, small vibrations will be generated, and their change characteristics are closely related to the coal rock stress and rupture deformation. Through the use of fluctuation principle, vibration-electricity conversion principle and other related theories combined with PVDF piezoelectric film technology, we independently developed a new type of equipment to convert the small vibration into voltage signal and collect it, and carried out uniaxial compression experiments on the composite coal rock under the conditions of different loading rates and different coal seam ratios to study the microseismic voltage evolution law at each stage of the deformation and rupture process of the loaded composite coal rock and obtain the microseismic characteristics and its deformation and rupture characteristics during the deformation and rupture process of the composite coal rock body. The microseismic characteristics of the composite coal rock in the process of deformation and rupture and the correlation between them and the rupture behavior of the coal rock body are investigated. The results show: The self-developed microseismic voltage acquisition equipment has high accuracy and sensitivity, and the acquired voltage data can be used as the basis for describing the microseismic characteristics of the loaded coal rock; under the condition of different loading rates of loaded composite coal rock, the process of stress change is positively correlated with the change of the microseismic voltage, and the microseismic voltage is more sensitive to the change of the loading rate compared with the stress; the evolution of microseismic voltage in each stress stage is different, the amplitude of microseismic voltage in the compression stage rises slowly from low, the microseismic voltage in the elasticity stage changes in the first and middle stages of the small fluctuations of irregular amplitude, and in the later stage of the microseismic voltage appears to fluctuate from low to high, the microseismic voltage fluctuations in the yield stage intensify in amplitude, and in the final stage there is a characteristic of the rupture precursor, and in the rupture stage there is a pulse amplitude of the microseismic voltage that is almost synchronized with the stress peak and returns to steady state rapidly after complete rupture of coal rock. the coal rock is completely ruptured, it quickly returns to a steady state; the increase of the proportion of composite coal rock combination leads to the increase of the amplitude distribution range and average amplitude of the main body of microseismic voltage, the peak voltage decreases, the amplitude number of the instantaneous voltage of the coal rock rupture decreases, and the overall distribution changes from dense to sparse. The tiny vibration generated by the loaded deformation and rupture process of the composite coal rock is converted into electrical signals and analyzed the change rule, and the correlation between the microseismic characteristics of the composite coal rock and the internal rupture behavior of the coal body is obtained, which provide new technological approaches for the safe production and sustainable development of the coal mining industry.